Some multivariate master polynomials for permutations, set partitions, and perfect matchings, and their continued fractions - Sokal, Alan D.; Zeng, Jiang (Advances in applied mathematics, 2022)
We find Stieltjes-type and Jacobi-type continued fractions for some “master polynomials” that enumerate permutations, set partitions or perfect matchings with a large (sometimes infinite) number of simultaneous statistics. Our results contain many previously obtained identities as special cases, providing a common refinement of all of them.